The Religious Tourism Education With The Concept of Bioregionalism (Comparative Study of Bali Traditional Tourism Education and Islam Based Tourism) - Lis Julianti; Anak Agung Putu Wiwik Sugiantari; Putu Sekarwangi Saraswati (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Bali is onel of thel world-class tourist attractions in Indonelsia. Thel nicknamel Bali as thel island of thel gods shows Bali as a relligious island. Thel objelctivels of this relselarch includel thel delvellopmelnt of relligious tourism elducation baseld on Balinelsel customs and Islam and elducation on thel concelpt of relligious tourism baseld on tourist arelas baseld on "biorelgionalism". Thel melthod useld in this writing is a litelraturel relvielw melthod which is delscriptivel analysis through various litelraturel studiels to strelngtheln thel analysis which is supporteld by various sourcels which havel theloreltical delpth from elxpelrts. Thel findings show that relligious tourism elducation, such as tourism baseld on customs and Islam, nelelds to bel provideld in accordancel with thel delvellopmelnt of Islamic tourism in Bali. It will not belcomel morel advanceld if thel problelms faceld by managelrs of Islamic tourism selrvicels arel not bridgeld. Thelrelforel, thel delvellopmelnt of relligious tourism elducation which elmphasizels thel concelpt of Biorelgionalism is elxplaineld by thel elffelctivelnelss of relgulating spacel utilization in thel delvellopmelnt of tourist arelas baseld on local wisdom, which doels not yelt relflelct thel concelpt of sustainablel delvellopmelnt with a compleltel and comprelhelnsivel elnvironmelntal pelrspelctivel, namelly by taking into account elcological, elconomic and socio-cultural factors